Increased mitochondrial emission of reactive oxygen species and calpain activation are required for doxorubicin‐induced cardiac and skeletal muscle myopathy. (23rd February 2015) - Min, Kisuk; Kwon, Oh‐Sung; Smuder, Ashley J.; Wiggs, Michael P.; Sollanek, Kurt J.; Christou, Demetra D.; Yoo, Jeung‐Ki; Hwang, Moon‐Hyon; Szeto, Hazel H.; Kavazis, Andreas N.; Powers, Scott K.
<x xml:space="preserve">Abstract</x> Key points Although doxorubicin is a highly effective anti‐tumour agent, the administration of this drug is associated with significant side effects, including contractile dysfunction and myopathy of both cardiac and skeletal muscles. The mechanism(s) responsible for doxorubicin‐induced contractile dysfunction and myopathy in cardiac and skeletal muscles remains unclear. In the present study, we report that increased mitochondrial oxidant production and calpain activation are major contributors to the development of doxorubicin‐induced myopathy. Moreover, treatment with a mitochondrial‐targeted peptide protects against doxorubicin‐induced mitochondrial dysfunction and myopathy in both heart and skeletal muscles. These experiments provide insight into the mechanisms responsible for DOX‐induced contractile dysfunction and myopathy in cardiac and skeletal muscles. Importantly, our results may provide the basis for developing therapeutic approaches to prevent doxorubicin‐induced cardiac and skeletal muscle myopathy. Abstract Although doxorubicin (DOX) is a highly effective anti‐tumour agent used to treat a variety of cancers, DOX administration is associated with significant side effects, including myopathy of both cardiac and skeletal muscles. The mechanisms responsible for DOX‐mediated myopathy remain a topic of debate. We tested the hypothesis that both increased mitochondrial reactive oxygen species (ROS) emission and activation of the cysteine protease calpain are required for DOX‐induced myopathy in rat cardiac and skeletal muscle. Cause and effect was determined by administering a novel mitochondrial‐targeted anti‐oxidant to prevent DOX‐induced increases in mitochondrial ROS emission, whereas a highly‐selective pharmacological inhibitor was exploited to inhibit calpain activity. Our findings reveal that mitochondria are a major site of DOX‐mediated ROS production in both cardiac and skeletal muscle fibres and the prevention of DOX‐induced increases in mitochondrial ROS emission protects against fibre atrophy and contractile dysfunction in both cardiac and skeletal muscles. Furthermore, our results indicate that DOX‐induced increases in mitochondrial ROS emission are required to activate calpain in heart and skeletal muscles and, importantly, calpain activation is a major contributor to DOX‐induced myopathy. Taken together, these findings show that increased mitochondrial ROS production and calpain activation are significant contributors to the development of DOX‐induced myopathy in both cardiac and skeletal muscle fibres.